Real estate cadastre in Ukraine - Gordieiev, A.; Plichko, L. (Land Management, Cadastre and Land Monitoring, 2025)
The article examines the process of creating a real estate cadastre in Ukraine and the directions of development based on the analysis of the experience and practices of the European Union. It is emphasized that the importance of correcting the misunderstandings created in this area of relations regarding the definition of real estate adopted in Ukraine and in the World, taking into account the recommendations of the World Bank on the unification of fragmented institutional approaches to property registration, its valuation and tax administration. The emphasis is on the continuous development of integration processes in this area in the EU countries and the World on the basis of a coordinated view of the future development of these systems, taking into account the conclusions drawn from the practice of implementing the future vision of the modern cadastre by 2014 and from the perspective of 2035, as well as on the importance of Ukraine’s accession to this process to create favorable conditions for the development of market relations and the activation of investment activities. It is determined that the strategic direction in the context of European integration is the harmonization of Ukraine’s cadastral policy with EU standards. It is proposed to continue the implementation of the Decree of the President of Ukraine on the cadastral system of 2003 by creating a multifunctional cadastre, which will include property rights registers, cadastral valuation of property and other state registers and cadastres. The article emphasizes the importance of unification and modernization of the system to increase its efficiency and compliance, based on proven modern practices, with international requirements. Keywords: real estate cadastre, cadastral system, European Union, land, real estate.